A PENGARUH SERVICE QUALITY, RELATIONSHP MARKETING DAN CUSTOMER SATISFACTION TERHADAP REVISIT INTENTION PADA LIA BEAUTY SALON - I Gusti Made Oka Astana (ARTHA SATYA DHARMA, 2022)
Abstract. The purpose of this study was to determine how : (1) the effect of service quality on revisit intention (2) the effect of relationship marketing on revisit intention (3) the effect of customer satisfaction on revisit intention. The research was conducted on customer of Lia Beaty Salon. This study uses a quantitative approach. The population in this studi is the customer of Lia Beauty Salon, number of sample is 85 respondens , the sampling technique was non probablity sampling method. . The sample are collected using questionnaires. Data analysis techniqued used in this study is a structural equation model (SEM) based in Partial Least Square ( PLS) with software version 3.3.3. The result of this study indicate that (1) service quality has a positif and significant effect on revisit intention, (2) relationship marketing has a positif and significant effect on revisit intention, (3) customer satisfaction has a positif and significant effect on revisit intention. Abstrak. Penelitian ini bertujuan untuk mengetahui: (1) Pengaruh service quality terhadap revisit intention, (2) Pengaruh relationship marketing terhadap revisit intention (3) Pengaruh customer satisfaction terhadap revisit intention. Penelitian ini dilakukan pada pelanggan Lia Beauty Salon. Penelitian ini menggunakan pendekatan kuantitatif. Populasi dalam penelitian ini adalah pelanggan Lia Beauty Salon. Sampel sebanyak 85 responden yang ditentukan dengan teknik non probability sampling. Pengumpulan data dilakukan dengan cara memberikan daftar pertanyaan dalam bentuk kuesioner kepada responden. Teknik analisis data yang digunakan dalam penelitian ini adalah dengan model persamaan Structural Equation Modeling (SEM) berbasis Partial Last Square (PLS) dengan versi software 3.3.3 Hasil penelitian menunjukkan bahwa (1) service quality berpengaruh positif dan signifikan terhadap revisit intention. (2) relationship marketing berpengaruh positif dan signifikan terhadap revisit intention. (3) customer satisfaction berpengaruh positif dan signifikan terhadap revisit intention